Review: Optimal Shock and Vibration Isolation - D.V. Balandin; N.N. Bolotnik; W.D. Pilkey (Shock and Vibration)
This is a review of the investigations into the field of optimum shock and vibration isolation, including the mathematical foundations of both optimal open-loop and optimal feedback isolation systems. This survey covers the literature from the initial studies to the present.